1999
DOI: 10.1016/s0022-0728(99)00379-4
|View full text |Cite
|
Sign up to set email alerts
|

Platinum–palladium loaded polypyrrole film electrodes for the electrooxidation of d-glucose in neutral media

Abstract: Modified polymer films with metal particles incorporated into the films by electrodeposition are known as possible electrocatalysts for various electrode reactions such as fuel cell applications. This work presents some results concerning the electrooxidation of D-glucose at modified polymer film electrodes prepared on a platinum substrate. This reaction has a great deal of interest in view of its applications to detection systems (glucose sensor), fuel cells (pacemakers) and electroorganic systhesis. The modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…In particular, there are a number of reports on the incorporation of noble metal particles in a polyaniline or polypyrrole matrix and the catalytic oxidation of carbohydrate molecules, such as glucose, at these particles [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, there are a number of reports on the incorporation of noble metal particles in a polyaniline or polypyrrole matrix and the catalytic oxidation of carbohydrate molecules, such as glucose, at these particles [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Becerik et al [4,12] have shown that more efficient oxidation of d-glucose occurs at palladium-or platinum-dispersed polypyrrole electrodes than at pure palladium or platinum substrates. Likewise, Guascito et al [3] have observed the oxidation of glucose in an alkaline NaOH solution at a copper-dispersed poly-3-methylthiophene substrate.…”
Section: Introductionmentioning
confidence: 99%
“…In order to check whether there is any effect of the Pt substrate on the oxidation of methanol on a Pt-dispersed PPy coated electrode, we carried out two types of experiments [9]: 1. We recorded the surface sensitive XPS spectra of Pt (substrate)/PPy and Pt (substrate)/PPy/Pt electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…Development of intrinsically conducting polymers [8] with almost metal-like charge transport properties has led to very efficient electrode materials. Polypyrrole (PPy) is one such conducting polymer used for electrocatalytic applications [9]. It is sufficiently conducting and stable under normal experimental conditions [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the oxidation of glucose on high gold content catalysts starts at a very low potential value (i.e. -0.5 V vs. SCE), which can easily be compared with values observed for catalysts such as Pt-Bi, Pt-Sn (Becerik & Kadirgan, 2001) or Pt-Pd (Becerik et al, 1999). …”
Section: Electrochemical Behaviour Of Gold-platinum Nanoparticles Towmentioning
confidence: 97%